Global Trends in Problem-Based Learning for Mathematics Learning in Primary Schools: A Bibliometric Study (2015-2025) - Kanisius Supardi; Farida Hanum; Agung Wahyu Hermansyah (Journal of Educational Studies, 2025)
Strengthening 21st-century competencies in elementary school mathematics learning is an urgent need in the era of the industrial revolution 4.0. Although Problem-Based Learning (PBL) is theoretically and empirically recognized as being able to improve students' learning outcomes and problem-solving abilities, existing research remains methodologically and thematically fragmented. This study aims to consolidate evidence and systematically map the development of PBL research trends in elementary school mathematics learning during the period 2015-2025. This study uses a mixed-methods sequential explanatory design that integrates bibliometric analysis and meta-analysis. Data of 285 documents were obtained from the Scopus database and analyzed using VOSviewer software, Bibliometrix R-package, and Comprehensive Meta-Analysis (CMA). The findings indicate that annual publication trends fluctuate significantly with research peaks occurring in 2018, 2020, 2022, and 2024. Geographically, Indonesia emerged as a major research center (global research hub) with the highest number of publications, while the United States played a role as a mediator for international collaboration. The thematic map identifies the primary research focus on the student pillar, mathematics content, and PBL methodology. This area of research is still in its infancy but not yet fully mature. There are significant research gaps in the specific cognitive mechanisms of PBL, as well as the need for teacher capacity building and the integration of advanced technologies such as intelligent tutoring systems in future research.